Effect of Dwikala Bhojan and Pathya Ahara in Prevention and Treatment of Sthaulya with special reference to Insulin Metabolism -A Case Report (International Journal of Food and Nutritional Sciences, 2022)
Obesity is a growing global issue, World Health Organization (WHO) proclaimed it a global epidemic, coining the term “globesity.” Dwikala bhojan and pathya ahara are two ayurvedic principles that can serve as a preventive, a curative aspect of dietary treatment and it is useful in treating sthaulya (obesity). The present case study investigated a 19-year-old female patient who visited the department of Swasthavritta and Yoga OPD at the KLE Ayurveda Hospital and medical research centre in Belagavi, Karnataka with primary complaints of weight gain, breathlessness, increased perspiration, and fatigue for eight months. The patient was given a one-month customized dietary regimen that incorporates the fundamental ideas of Dwikala bhojana, Aharaj pathya, and viharaj pathya. After the treatment, there was a substantial difference in anthropometric measurements, fat analysis, and blood insulin levels. After this intervention, the intensity of breathlessness, increased perspiration, and fatigue also decreased.